Three-dimensional viscoelastic time-domain finite-difference seismic modelling using the staggered Adams–Bashforth time integrator. Issue 3 (3rd February 2016) - Bohlen, Thomas; Wittkamp, Florian
Abstract: We analyse the performance of a higher order accurate staggered viscoelastic time-domain finite-difference method, in which the staggered Adams–Bashforth (ABS) third-order and fourth-order accurate time integrators are used for temporal discretization. ABS is a multistep method that uses previously calculated wavefields to increase the order of accuracy in time. The analysis shows that the numerical dispersion is much lower than that of the widely used second-order leapfrog method. Numerical dissipation is introduced by the ABS method which is significantly smaller for fourth-order than third-order accuracy. In 1-D and 3-D simulation experiments, we verify the convincing improvements of simulation accuracy of the fourth-order ABS method. In a realistic elastic 3-D scenario, the computing time reduces by a factor of approximately 2.4, whereas the memory requirements increase by approximately a factor of 2.2. The ABS method thus provides an alternative strategy to increase the simulation accuracy in time by investing computer memory instead of computing time.